Analisis Iklim Organisasi Dalam Meningkatkan Kepuasan Kerja Pegawai Di Kantor Satuan Polisi Pamong Praja Kota Gunungsitoli - Zebua, Berkat Putra; Bate'e, Maria Magdalena; Waruwu, Eliyunus (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study aims to analyze the organizational climate in an effort to increase employee job satisfaction at the Gunungsitoli City Pamong Praja Police Unit Office. The focus of this research includes three main aspects: employee responsibility in carrying out duties, warm atmosphere between employees, and support from leaders. This research is motivated by the observation of the lack of responsibility, warm atmosphere, and leadership support that has the potential to affect the level of employee job satisfaction. The research method used is descriptive with a quantitative approach, where data is collected through questionnaires distributed to employees at the Gunungsitoli City Pamong Praja Police Unit Office. The results of the study show that the level of responsibility, warm atmosphere, and support from leaders in the office still needs to be improved to achieve optimal job satisfaction. This research is expected to contribute to the development of theories and practices regarding organizational climate, especially in the context of local government agencies. In addition, the results of this study are also expected to be a reference for further research and provide insight for the leaders of related agencies in increasing employee job satisfaction.